(3GdJHUQIs - (3CHh GdMSf Ydj Hf eMeO GdQHYi GddNeis; (3YHO GdQMef Hf GdbGSe Hf NGdO Hf LfGOI GdYJbqj GdeGdcj GdeUQj, CHh YHO Gddg, hjYQa HGHf GdbGSe,J (B191 (3g` s
(3ChdgG (B:s
(3cJGH GdUQa GdQHG eMQe HGdbQBf hGdSfI hGdELeGY s
(3BNQgG (B:s
(3ef HGH ai GdhcGdI Ydi HjY GdQgf Ke jNJdaGf hjZQegG hjCNP KhHg dCfg hGgH , aGdbhd bhdg Cfg de jgH EdG eG CbQHg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B681s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda (B: 518s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3Gdabg GdeGdcjs